Estimating Carbon Stock in the Padang Sugihan Wildlife Sanctuary Forest Using Allometric Models and Sentinel-2A Imagery: Estimasi Cadangan Karbon di Hutan Suaka Margasatwa Padang Sugihan Menggunakan Pendekatan Alometrik dan Citra Satelit Sentinel-2A - Atep Edi Hikmana; M. Umar Harun; Sarno; Jun Harbi (Journal of Global Sustainable Agriculture, 2025)
Peat swamp forests in South Sumatra play a vital role in climate change mitigation through carbon storage and hydrological regulation. However, anthropogenic pressures such as illegal logging, land conversion, and recurring fires have led to severe ecosystem degradation, including within the Padang Sugihan Wildlife Reserve, which covers approximately 86,932 hectares. This reserve serves as a critical habitat for endemic flora and fauna but has experienced a decline in forest cover and ecological functions, ultimately affecting its carbon storage capacity. This study aimed to estimate vegetation density and carbon stock through a combination of field observations, spatial analysis (land cover change, NDVI, and carbon stock), and allometric approaches. Eight plots measuring 20×20 m were established based on the 2024 land cover map, representing similar secondary forest vegetation structures. The analysis followed SNI 7724:2011 standards for carbon stock measurement and calculation. The results revealed significant land cover changes between 2020 and 2024, including a reduction in secondary peat swamp forest and an increase in open areas, plantations, and water bodies. NDVI values and allometric measurements indicated spatial variations reflecting vegetation growth dynamics and carbon absorption potential. Plot 8 and Locus 4 recorded the highest carbon accumulation, at 1.602 and 10.63 tons CO₂e ha⁻¹, respectively, influenced by the dominance of Mahang species (Lauraceae family), vegetation density, and stand age. These findings highlight the critical role of secondary peat swamp forests in maintaining carbon balance and supporting peatland ecosystem restoration at the landscape level. The results also provide scientific evidence for developing sustainable management and conservation strategies for the Padang Sugihan Wildlife Reserve.